Gender Differences in Recurrent Mental Health Contact After a Hospitalization for Interpersonal Violence: Western Australia, 1997 to 2008 - Meuleners, Lynn; Fraser, Michelle (Sage Publications, 2014)
Interpersonal violence and mental illness are significant public health issues. This study aimed to determine gender differences in risk factors for recurrent mental health contacts after a hospitalization for interpersonal violence in Western Australia between 1997 and 2008. This population-based retrospective cohort study used linked hospital morbidity data and mental health records to identify individuals who were hospitalized due to interpersonal violence and had recurrent mental health contacts following hospitalization. A total of 1,969 individuals had a first-ever mental health contact after their index hospitalization for violence. The most common reasons for a mental health contact after interpersonal violence hospitalization were anxiety and/or depression (n = 396, 20.1%), neurotic disorders (n=338, 11.8%), schizophrenia (n=232, 11.8%), and psychoactive substance use (n = 206, 10.5%). Different risk factors for recurrent contact with mental health services emerged for males and females. For males, factors significantly associated with increased risk of recurrent mental health contacts included advancing age and not being married. However, for females, type of violence, Indigenous status, age, and living in rural or remote areas affected the risk of recurrent mental health contacts, whereas marital status did not. These findings have implications for the targeting of mental health prevention programs tailored specifically for males and females affected by violence.